2021
DOI: 10.3390/ma14071653
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamic Tensile Behaviour of Thermoplastic Composite Carbon/Polyamide 6.6 Using Split Hopkinson Pressure Bar

Abstract: A dynamic tensile experiment was performed on a rectangular specimen of a non-crimp fabric (NCF) thermoplastic composite T700 carbon/polyamide 6.6 specimens using a split Hopkinson pressure (Kolsky) bar (SHPB). The experiment successfully provided useful information on the strain-rate sensitivity of the NCF carbon/thermoplastic material system. The average tensile strength at three varying strain rates: 700, 1400, and 2100/s was calculated and compared to the tensile strength measured from a standardized (quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Bondy and Altenhof [22] carried out an LVI test on 600 mm × 600 mm CFRTP (carbon/PA6.6) panels using a 60 kg carriage and a 20 mm impactor with a mean impact velocity of 4.4 m/s, which resulted in an impact energy of 570 J. Strain-rate sensitivity was also reported on the carbon/PA6.6 material system [22]-550% higher stiffness was observed in LVI versus quasi-static loading. This supported the claim made by Mohsin et al [23] for virtually identical CFRTP system. However, the studies reported in [21,22] are not directly applicable to the automotive or aerospace industry as the impactor mass is too high and the impact velocity is too low (despite the high impact energy).…”
Section: Characterisation Of Impact Behaviour Of Thermoplastic Compositessupporting
confidence: 90%
See 1 more Smart Citation
“…Bondy and Altenhof [22] carried out an LVI test on 600 mm × 600 mm CFRTP (carbon/PA6.6) panels using a 60 kg carriage and a 20 mm impactor with a mean impact velocity of 4.4 m/s, which resulted in an impact energy of 570 J. Strain-rate sensitivity was also reported on the carbon/PA6.6 material system [22]-550% higher stiffness was observed in LVI versus quasi-static loading. This supported the claim made by Mohsin et al [23] for virtually identical CFRTP system. However, the studies reported in [21,22] are not directly applicable to the automotive or aerospace industry as the impactor mass is too high and the impact velocity is too low (despite the high impact energy).…”
Section: Characterisation Of Impact Behaviour Of Thermoplastic Compositessupporting
confidence: 90%
“…The raw materials were supplied by THERMOCOMP project [6] partners. The T700/PA6.6 material system has also previously been reported and discussed in Mohsin et al [23].…”
Section: Materials System and Preparationmentioning
confidence: 76%
“…These materials were supplied by partners in the THERMOCOMP project [ 29 ]. The T700/PA6.6 material system has also previously been reported and discussed in Mohsin et al [ 24 , 32 ].…”
Section: Methodsmentioning
confidence: 87%
“…Once the strain rate is beyond this value, a higher slope of the rate sensitivity is shown. Note that, as the test points of the dynamic compression and tensile loading at the ambient temperature are close, the material can be approximately treated as “isotropic”, and one single bi-linear fitting is there given for ambient temperature tests [ 27 , 28 ].…”
Section: Discussion On the Dynamic Yield Stressmentioning
confidence: 99%